CLOUD TECHNOLOGIES REVOLUTIONIZING AI DEVELOPMENT: A TECHNICAL PERSPECTIVE - Anshul Goel, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive technical article examines the transformative impact of cloud technologies on artificial intelligence development and deployment. The article explores how cloud computing has revolutionized the AI landscape by democratizing access to high-performance computing resources and enabling scalable, cost-effective solutions. It investigates key aspects including advanced computing architectures, data management systems, security protocols, and collaborative development environments. The article highlights the evolution from traditional on-premises infrastructure to dynamic cloud-based solutions, emphasizing how this transition has particularly benefited smaller organizations and startups. The article covers crucial areas such as AutoML platforms, enterprise data solutions, business intelligence integration, and emerging trends in edge computing and quantum technologies. Through examination of real-world implementations and industry case studies, this article demonstrates how cloud technologies have not only reduced barriers to AI adoption but also enhanced operational efficiency, improved security measures, and accelerated innovation across various sectors, while addressing the challenges and considerations organizations face in this rapidly evolving technological landscape.